Enhancing construction site performance through technology and management practices as material waste mitigation in the Malaysian construction industry - Mohammed Abdullah Abkar, Mahdi; Yunus, Riduan; Gamil, Yaser; Albaom, Mohammed Abdo (Cel Press, 2024)
The construction industry, increasingly prioritizing sustainability, necessitates an exploration of technology and management’s role in mitigating material waste at construction sites. This study examines the impact of 3R, IBS, BIM, and MMA in enhancing Construction Site Performance (CSP) in the Malaysian construction sector. Seven hypotheses were formulated to assess the relationship between technology adoption, material management practices, and the moderating influence of Material Management Adoption (MMA) on CSP. Data were collected through an online survey from 295 valid responses in the Malaysian construction sector, focusing on professionals involved in solid waste management. Utilizing Partial Least Squares - Structural Equation Modeling (PLS-SEM) and Statistical Package for the Social Sciences (SPSS), the findings highlight the importance of technological integration, efficient material management, and competitive strategies in effective material waste mitigation. Furthermore, the qualitative aspect of the study, conducted among 6 solid waste organizations in Malaysia, enriches the findings by providing nuanced insights into local practices and challenges. Emphasizing the importance of contextual insights, the study addresses professionals involved in solid waste management within the Malaysian construction industry. The geographical specificity adds depth to the analysis, offering a comprehensive understanding of regional dynamics. Despite acknowledging limitations in technology and material usage, the study offers recommendations for refining waste mitigation and improving construction site performance. This research model offers actionable insights for construction site stakeholders, emphasizing the criticality of waste mitigation and CSP. The results, both quantitative and qualitative, underscore the potential of these practices within the Malaysian construction industry to foster innovation and drive positive change.